2007
DOI: 10.1097/hjh.0b013e3280103a5a
|View full text |Cite
|
Sign up to set email alerts
|

The functional variant of the CLC-Kb channel T481S is not associated with blood pressure or hypertension in Swedes

Abstract: Our data do not support a role of the CLC-Kb T481S polymorphism in BP regulation in Swedes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Several more recent studies with larger sample groups have not found a link with hypertension [10][11][12]. Our data appears to confirm this observation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several more recent studies with larger sample groups have not found a link with hypertension [10][11][12]. Our data appears to confirm this observation.…”
Section: Discussionsupporting
confidence: 82%
“…However, the small size of their study population leaves room for uncertainty [13]. Our findings agree with a recent study of larger sample size and add further evidence that this polymorphism is not a predictor of BP [12].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This suggestion is further supported by the observation of an association between a common ClC-Kb polymorphism that increases channel activity and a predisposition to hypertension (7,37,62,73,126). However, it should be noted that such a predisposition has not been detected in all studies (17,37,73,132). It has been suggested that salt-loading conditions as well as sex and ethic segregation need to be considered, and that larger studies are necessary to resolve the issue (73,126,150).…”
Section: Clc-ka/bmentioning
confidence: 58%
“…The low blood pressure associated with defective ClC-Kb function suggests ClC-Kb is a target for antihypertensive drugs (41,81). This suggestion is further supported by the observation of an association between a common ClC-Kb polymorphism that increases channel activity and a predisposition to hypertension (7,37,62,73,126). However, it should be noted that such a predisposition has not been detected in all studies (17,37,73,132).…”
Section: Clc-ka/bmentioning
confidence: 68%